Resilient cooperators stabilize long-run cooperation in the finitely repeated Prisoner’s Dilemma - Andrew Mao (Nature Portfolio, 2017)
Studying the dynamics of learning in repeated games of cooperation is complicated by the short duration of traditional experiments. Here the authors perform a virtual prisoner's dilemma game over twenty consecutive days, finding that a minority of resilient co-operators can sustain cooperation indefinitely.